Encyclopedia of Catalysis 2011
DOI: 10.1002/0471227617.eoc108.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hydroformylation—Homogeneous

Abstract: The hydroformylation or oxo‐synthesis is one of the most important transition metal assisted homogeneous catalytic transformation, providing industrial‐scale production of aldehydes and alcohols. The hydroformylation—homogeneous article presents the basic chemistry and kinetics of hydroformylation, solvents of hydroformlylation, and side reactions accompanying hydroformylation. The detailed reaction mechanisms related to the cobalt‐ and rhodium‐modified and unmodified catalysts are presented as well. The chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 248 publications
0
3
0
Order By: Relevance
“…The first carbonylation reaction, which led to the formation of aldehydes by the reaction of a carbon‐carbon double bond with carbon monoxide and dihydrogen in the presence of a transition metal catalyst, was discovered by German chemist Otto Roelen in 1938. [ 17‐18 ] The accidental discovery of CO addition to olefinic bond of ethylene [ 19 ] was made during the development of the cobalt‐catalyzed Fischer‐Tropsch reaction, while the formation of propanal was observed from ethylene and syngas (H 2 : CO = 1 : 1). The product yield became less and less by increasing the temperature indicating the presence of a temperature‐sensitive species [HCo(CO) 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first carbonylation reaction, which led to the formation of aldehydes by the reaction of a carbon‐carbon double bond with carbon monoxide and dihydrogen in the presence of a transition metal catalyst, was discovered by German chemist Otto Roelen in 1938. [ 17‐18 ] The accidental discovery of CO addition to olefinic bond of ethylene [ 19 ] was made during the development of the cobalt‐catalyzed Fischer‐Tropsch reaction, while the formation of propanal was observed from ethylene and syngas (H 2 : CO = 1 : 1). The product yield became less and less by increasing the temperature indicating the presence of a temperature‐sensitive species [HCo(CO) 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The product yield became less and less by increasing the temperature indicating the presence of a temperature‐sensitive species [HCo(CO) 4 ]. [ 19 ] At the same time and in Germany as well, Walter Reppe revealed that methanol could be carbonylated in the presence of metal carbonyls of VIIIB elements as catalysts. [ 20 ] However, the reaction requires extremely high pressure (up to 700 bar) and temperature ( ca .…”
Section: Introductionmentioning
confidence: 99%
“…Hydroformylation (oxo process), discovered by Otto Roelen as far back as 1938, is still widely used to produce aldehydes, which can further be converted into alcohols, ethers and esters, carboxylic acids, aliphatic amines, and other derivatives with high added value [1]. The modern industrial hydroformylation process is based on homogeneous rhodium systems [2][3][4][5]. However, one of the main problems of homogeneous hydroformylation has long been the difficulty of the recovery of the catalyst from the reaction mixture and the purification of the catalyst.…”
Section: Introductionmentioning
confidence: 99%